HETEROLOGOUS EXPRESSION AND CHARACTERIZATION OF HUMAN ERYTHROPOIETIN IN PICHIA PASTORIS - SANTOSO A; RUBIYANA Y; WIJAYA SK; HERAWATI N; WARDIANA A; NINGRUM RA (International Journal of Pharma and Bio Sciences, 2013)
Recombinant human erythropoietin (EPO) is a glycoprotein produced as a therapeutic agent for the treatment of anemia associated with severe kidney damage. The demand of this protein currently met by recombinant expression in mammalian cells. Pichia pastoris has become popular yeast based protein production systems to substitute mammalian expression systems. In this study, recombinant human EPO (rhEPO) protein obtained by expressing the human epo gene in methylotropic yeast P. pastoris, strain X33. The human EPO cDNA was inserted into pPICZαB vector, under the control of AOX1 promoter, and fused with a polyhistidine tag and c-myc epitope. Several clones were screened by Western blot analysis using polyclonal anti-EPO antibodies. The highest expressing clone was selected for subsequent study. The recombinant human EPO (rHuEPO) protein produced was approximately 37 kDa in size. Analyses by SDS/PAGE, Western blot, deglycosylation and internal amino acid sequencing confirmed the authenticity of the expressed rHuEPO protein.